Fe-BASED NANOCRYSTALLINE SOFT MAGNETIC ALLOY CORE, MAGNETIC COMPONENT, AND METHOD FOR MANUFACTURING Fe-BASED NANOCRYSTALLINE SOFT MAGNETIC ALLOY CORE
Patent Information
- Application Number
- JP2023127238
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0009】 本開示によれば、高周波領域において高い透磁率を示すFe基軟磁性合金磁心を提供することができる。
Smart Images

Figure 2025022552000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an Fe-based nanocrystalline, soft magnetic alloy, a magnetic component, and a method for producing an Fe-based nanocrystalline, soft magnetic alloy. [Background technology]
[0002] In recent years, there has been active promotion of high performance, miniaturization, and weight reduction of electrical and electronic devices and information and communication devices. Accordingly, there is a demand for miniaturization of power conversion units such as noise filters used in the above devices, but magnetic components for noise filters, such as common mode choke coils, cannot be miniaturized without increasing the magnetic permeability of the material. In addition, in order to improve the performance, miniaturization, and weight reduction of the above devices, semiconductors such as GaN and SiC are used in switching power supplies, and the conversion frequency is becoming higher, but the noise generated according to the conversion frequency is also becoming higher.
[0003] Under these circumstances, there is a demand for magnetic materials used, particularly in common mode choke coils, to exhibit higher magnetic permeability in higher frequency ranges.
[0004] So far, an Fe-Si-Al based soft magnetic alloy called Sendust has been reported as a magnetic material that exhibits excellent high frequency characteristics (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2004-002949 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present disclosure has been made in consideration of the above problems, and aims to provide an Fe-based soft magnetic alloy core that exhibits high magnetic permeability in the high frequency range.
Means for Solving the Problem
[0007] As a result of repeated studies to solve the above problems, the present inventors have found that an Fe-based soft magnetic alloy core exhibiting high permeability in the high-frequency region can be obtained by using an Fe-Si-Al-based soft magnetic alloy containing Ni as a material constituting the magnetic core. That is, the gist of the present disclosure is as follows.
[0008] [1] A magnetic core formed by winding a ribbon made of an Fe-based nanocrystalline soft magnetic alloy containing an amorphous phase and a crystalline phase, The Fe-based nanocrystalline soft magnetic alloy has a composition represented by the following compositional formula (I), and is an Fe-based nanocrystalline soft magnetic alloy core. (Fe 1-x-y Si x Al y ) 100-a-b-c-d Ni a M b M' c Cu d (I) (In the compositional formula (I), M is one or more elements selected from the group consisting of Nb, W, Zr, Hf, Ti, and Mo; M' is one or more elements selected from the group consisting of B, C, and P; a, b, c, and d are in atomic %, respectively, 0.5 < a < 5.0, 2.0 ≤ b ≤ 5.0, 3 .0 < c < 10.0 and 0 < d < 3.0; x and y are 0.100 ≤ x ≤ 0.320 and 0.010 ≤ y ≤ 0.100, respectively, and satisfy 0.190 ≤ x + y ≤ 0.320.) [2] The Fe-based nanocrystalline soft magnetic alloy core according to [1], wherein a in the compositional formula (I) satisfies 1.0 ≤ a ≤ 4.0. [3] The Fe-based nanocrystalline soft magnetic alloy core according to [1], wherein a in the compositional formula (I) satisfies 1.5 ≤ a ≤ 4.0. [4] The Fe-based nanocrystalline, soft magnetic alloy core according to [1], wherein a in the composition formula (I) satisfies 2.0≦a≦3.0. [5] The Fe-based nanocrystalline, soft magnetic alloy core according to any one of [1] to [4], wherein the average crystallite size of the crystalline phase is 12.0 nm or less. [6] Clusters are dispersed in the amorphous phase, and the number density of the clusters is 3.0×10 -4 / nm 3 The Fe-based nanocrystalline, soft magnetic alloy core according to any one of [1] to [5] above. [7] A magnetic component having an Fe-based nanocrystalline, soft magnetic alloy core according to any one of [1] to [6]. [8] A method for producing an Fe-based nanocrystalline soft magnetic alloy core according to any one of [1] to [6], a ribbon-producing step of producing a ribbon of an amorphous alloy by rapidly solidifying the molten metal having the composition represented by the general formula (I) by a super-quenching method; a heat treatment step of heat treating the ribbon; The present invention relates to a method for producing an Fe-based nanocrystalline soft magnetic alloy core. [9] The method for producing an Fe-based nanocrystalline, soft magnetic alloy core according to [8], wherein the heat treatment step is carried out under a magnetic field application condition. Effect of the Invention
[0009] According to the present disclosure, it is possible to provide an Fe-based soft magnetic alloy core that exhibits high magnetic permeability in the high frequency range. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph showing the relationship between the Ni content in the Fe-based nano-crystalline, soft magnetic alloy constituting the Fe-based nano-crystalline, soft magnetic alloy magnetic cores obtained in the examples and comparative examples, and the relative permeability of the Fe-based nano-crystalline, soft magnetic alloy magnetic cores at 1 MHz. [Diagram 2]1 is a graph showing the relationship between the Ni content in the Fe-based nano-crystalline, soft magnetic alloy constituting the Fe-based nano-crystalline, soft magnetic alloy magnetic cores obtained in the examples and comparative examples and the average crystallite size of the crystalline phase in the Fe-based nano-crystalline, soft magnetic alloy. [Diagram 3] 1 is a three-dimensional map (photograph in lieu of drawing) of the Fe-based nanocrystalline, soft magnetic alloy constituting the Fe-based nanocrystalline, soft magnetic alloy magnetic cores obtained in the examples and comparative examples. [Figure 4] 1 is a graph showing the relationship between the Ni content in the Fe-based nano-crystalline, soft magnetic alloy constituting the Fe-based nano-crystalline, soft magnetic alloy magnetic core obtained in the example and the relative permeability of the Fe-based nano-crystalline, soft magnetic alloy magnetic core. [Diagram 5] 1 is a polarizing microscope photograph (drawing substitute photograph) of a magnetic domain structure of an Fe-based nano-crystalline, soft magnetic alloy constituting an Fe-based nano-crystalline, soft magnetic alloy magnetic core obtained in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The following is a detailed description of the embodiments of the present disclosure. The following description of the components is an example (representative example) of the embodiments of the present disclosure, and the present disclosure is not limited to these contents as long as it does not exceed the gist of the disclosure. In this specification, when "~" is used with a numerical value or a physical property value before and after it, the values before and after it are included.
[0012] 1. Fe-based nanocrystalline soft magnetic alloy core An Fe-based nanocrystalline, soft magnetic alloy core according to an embodiment of the present disclosure (hereinafter, may be simply referred to as a "magnetic core") is a magnetic core formed by winding a ribbon made of an Fe-based nanocrystalline, soft magnetic alloy containing an amorphous phase and a crystalline phase. The Fe-based nanocrystalline, soft magnetic alloy core according to the present embodiment exhibits high magnetic permeability in the high frequency range by using a ribbon made of an Fe-based nanocrystalline, soft magnetic alloy containing specific amounts of Al and Ni.
[0013] In the present disclosure, "relative magnetic permeability" may be used as an index for evaluating "magnetic permeability." In addition, in the present disclosure, the magnetic permeability in the high frequency range is evaluated based on the magnetic permeability at a frequency of 1 MHz in consideration of the background that the conversion frequency is becoming higher. The Fe-based nanocrystalline soft magnetic alloy core according to the present embodiment exhibits a high relative magnetic permeability at 1 MHz, for example, 4,000 or more, 4,500 or more, 5,000 or more, or 5,500 or more.
[0014] The relative permeability of an Fe-based nanocrystalline, soft magnetic alloy core is calculated, for example, based on the following formula (1) by measuring the inductance of a coil wound around an Fe-based nanocrystalline, soft magnetic alloy core. μr=μ / μ0 (1) μr: relative permeability μ0: Magnetic permeability of vacuum = 4π×10 -7 [H / m] μ: Magnetic permeability [H / m]=Ll / A / N 2 L: Inductance [H] l: Magnetic path length [m] A: Core effective cross-sectional area [m 2 ] N: Number of turns
[0015] 1-1.Fe-based nanocrystalline soft magnetic alloy ribbon The ribbon forming the Fe-based nanocrystalline, soft magnetic alloy core according to the present embodiment is made of an Fe-based nanocrystalline, soft magnetic alloy containing an amorphous phase and a crystalline phase. Clusters may be dispersed in the amorphous phase.
[0016] 1-1-1. Composition of Fe-based nanocrystalline soft magnetic alloy The Fe-based nanocrystalline, soft magnetic alloy has a composition represented by the following composition formula (I): This composition may contain unavoidable impurities such as Cr and Mn. (Fe 1-x-y S x Al y ) 100-a-b-c-d Ni a M b M' c Cu d (I)
[0017] (M) In the composition formula (I), M is one or more elements selected from the group consisting of Nb, W, Zr, Hf, Ti and Mo, and is preferably Nb. Nb is considered to have the effect of making the precipitated crystallites fine by forming a grain boundary layer of the amorphous phase together with B during nanocrystallization, or by suppressing the growth of crystallites through interaction with elements such as Cu that can form clusters and lower the crystallization onset temperature.
[0018] (M') In the composition formula (I), M' is one or more elements selected from the group consisting of B, C, and P. When the Fe-based nanocrystalline soft magnetic alloy contains a certain amount of one or more elements selected from the group consisting of B, C, and P together with Si, an amorphous structure in which the constituent elements are uniformly dispersed is easily formed. Of the above elements, M' is preferably B.
[0019] (a, b, c and d) a, b, c and d respectively represent the contents [atomic %] of Ni, M, M' and Cu in the composition formula (I).
[0020] a is usually more than 0.5, preferably 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more, and is usually less than 5.0, preferably 4.0 or less, and more preferably 3.0 or less. By setting a within the above range, the magnetic permeability of the Fe-based nanocrystalline, soft magnetic alloy core at 1 MHz can be improved, as shown in the examples described later. Also, as shown in the examples described later, when a is set to 1.0 or more, the cluster number density increases, and a crystal phase with a smaller average crystallite size than that of an Fe-based nanocrystalline, soft magnetic alloy that does not contain Ni tends to be formed.
[0021] b is usually 2.0 or more, preferably more than 2.0, more preferably 2.5 or more, even more preferably 3.0 or more, and usually 5.0 or less, preferably less than 5.0, more preferably 4.5 or less, even more preferably 4.0 or less. b is most preferably about 3.0.
[0022] c is usually more than 3.0, preferably 4.0 or more, more preferably 4.5 or more, and even more preferably 5.0 or more, and is usually less than 10.0, preferably 9.0 or less, more preferably 8.0 or less, and even more preferably 7.0 or less. When M' is B, by setting c within the above range, the amorphous forming ability is ensured, and the precipitation of Fe-B binary compounds, which have inferior magnetic properties, is suppressed, thereby improving the soft magnetic properties.
[0023] d is usually more than 0, preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.7 or more, and is usually less than 3.0, preferably 2.5 or less, more preferably 2.0 or less, even more preferably 1.5 or less, and particularly preferably 1.2 or less. d is 1.0 It is most preferable that the amount is about 100%. By setting d within the above range, the amorphous forming ability is ensured, and the amorphous alloy can be easily produced by the ultra-quenching method described later. In addition, by setting d within the above range, clusters containing Cu are uniformly formed in the amorphous phase prior to the crystallization of α-Fe(Si,Al,Ni), and the clusters tend to become crystal nuclei and form fine crystal phases.
[0024] In addition, by setting a, b, c, and d within the above ranges, a crystalline phase with a small average crystallite size is formed, and the coercive force of the Fe-based nanocrystalline soft magnetic alloy core is reduced, so that the magnetic permeability of the Fe-based nanocrystalline soft magnetic alloy core tends to be improved.
[0025] (x and y) x and y respectively represent the molar amounts of Si and Al when the total molar amount of Fe, Si, and Al in the Fe-based nanocrystalline, soft magnetic alloy is taken as 1. In addition, when the total molar amount of Fe, Si, and Al in the Fe-based nanocrystalline, soft magnetic alloy is taken as 1, the molar amount of Fe is expressed as 1-(x+y).
[0026] x is usually 0.100 or more, preferably 0.110 or more, more preferably 0.140 or more, even more preferably 0.160 or more, and is usually 0.320 or less, preferably 0.300 or less, more preferably 0.250 or less, even more preferably 0.200 or less, and particularly preferably 0.180. By setting x within the above range, the amorphous forming ability is ensured, making it easier to prepare an amorphous alloy by the ultra-rapid cooling method described later, and also suppressing an excessive increase in the crystal magnetic anisotropy in the crystal phase, thereby improving the soft magnetic properties.
[0027] y is usually 0.010 or more, preferably 0.020 or more, more preferably 0.030 or more, and even more preferably 0.040 or more, and is usually 0.100 or less, preferably 0.090 or less, more preferably 0.080 or less, even more preferably 0.070 or less, and particularly preferably 0.060 or less. By setting y within the above range, the crystalline magnetic anisotropy of the crystalline phase of the Fe-Si-Al-Ni quaternary alloy within the crystalline phase is reduced, which reduces the crystalline magnetic anisotropy of the Fe-based nanocrystalline soft magnetic alloy and tends to improve soft magnetic properties such as magnetic permeability and coercive force.
[0028] In addition, x+y is usually 0.190 or more, preferably 0.200 or more, more preferably 0.210 or more, and is usually 0.320 or less, preferably 0.280 or less, more preferably 0.250 or less, and even more preferably 0.230 or less.
[0029] The Fe-based nanocrystalline, soft magnetic alloy core according to the present embodiment is formed from a ribbon of an Fe-based nanocrystalline, soft magnetic alloy containing a specific amount of Ni and Al, and therefore exhibits high magnetic permeability in the high frequency range such as 1 MHz. The inventors speculate that the reason for this is as follows.
[0030] Usually, when a nanocrystalline soft magnetic alloy contains Ni, it is believed that the crystal magnetic anisotropy of the crystal phase increases and the coercive force increases. However, in this embodiment, since the Fe-based nanocrystalline soft magnetic alloy contains Al, it is believed that the action of Al can alleviate the crystal magnetic anisotropy increased due to Ni. In addition, Ni reacts with Al to produce an intermetallic compound, and this intermetallic compound forms many clusters together with Cu and the like. By forming many clusters, the distance between the crystals becomes closer and the growth of each crystal is suppressed, so that a crystal phase with a small average crystallite size can be generated. And, since the average crystallite size is small, the exchange interaction is strengthened and the coercive force is reduced in proportion to the average crystallite size, so that it is believed that the effect of the increase in coercive force due to Ni is alleviated, or the effect of the reduction in coercive force due to the refinement of the average crystallite size exceeds the effect of the increase in coercive force due to Ni. Therefore, it is believed that the Fe-based nanocrystalline soft magnetic alloy core according to this embodiment exhibits a higher magnetic permeability than the magnetic core of an Fe-based nanocrystalline soft magnetic alloy containing Ni but not Al.
[0031] In addition, when the nanocrystalline soft magnetic alloy contains Ni, the spontaneous magnetization of Ni gives induced magnetic anisotropy, and the induced magnetic anisotropy with different directions depending on the location is given, which forms a complex magnetic domain structure and makes it difficult for the magnetic domain walls to move, compared to when the nanocrystalline soft magnetic alloy does not contain Ni. This increases the effect of magnetization rotation in the magnetization process, and it is presumed that the magnetic permeability in the high frequency range of the Fe-based nanocrystalline soft magnetic alloy core according to this embodiment is improved.
[0032] 1-1-2. Crystalline phases and crystallites The crystallites are composed of a crystalline phase of an Fe-Si-Al-Ni quaternary alloy having a body-centered cubic structure (bcc structure), in which Si, Al and Ni are dissolved in the Fe as a main component, and other elements may also be dissolved in the Fe as a solid solution. The crystallite structure is identified by X-ray diffraction (XRD).
[0033] The average crystallite size of the crystalline phase is not particularly limited as long as it is nanoscale, and is preferably 5.0 nm or more, more preferably 6.0 nm or more, even more preferably 7.0 nm or more, and also preferably 12.0 nm or less, more preferably 11.0 nm or less, even more preferably 10.0 nm or less, and particularly preferably 9.0 nm or less. The average crystallite size of the crystalline phase can be adjusted within a desired range by adjusting a, b, c, d, and y in the composition formula (I), but among these, a, d, and y, that is, the content of Ni, Cu, and Al in the Fe-based nanocrystalline soft magnetic alloy, are highly correlated with the average crystallite size of the crystalline phase, so the average crystallite size of the crystalline phase can be easily adjusted by adjusting a, d, and y.
[0034] By setting the average crystallite size of the crystalline phase within the above range, the crystalline magnetic anisotropy is averaged and reduced, the effect of improving the magnetic permeability is increased, and the soft magnetic properties such as the coercive force also tend to improve.
[0035] The average crystallite size of the crystalline phase is determined by analyzing an Fe-based nanocrystalline soft magnetic alloy with an X-ray diffractometer (XRD) and according to the following formula (2). D = (K × λ) / (β × cosθ) (2) D: Crystallite size [nm] K: Scherrer constant λ: wavelength of X-rays [nm] β: Half-width [rad] θ: Bragg angle [rad]
[0036] 1-1-3. Cluster Clusters may be dispersed in the amorphous phase. The term "cluster" refers to an assembly of atoms observed by a three-dimensional atom probe (3DAP). The clusters may be distributed uniformly or unevenly in the Fe-based nanocrystalline soft magnetic alloy, but are preferably distributed uniformly.
[0037] The type of atoms constituting the cluster is not particularly limited as long as it is an atom other than Fe, which is the main component of the Fe-based nanocrystalline soft magnetic alloy, and may be one or more atoms selected from the group consisting of Si, Al, Ni, Nb, W, Zr, Hf, Ti, Mo, B, C, P, and Cu. Of these, the atoms constituting the cluster preferably include one or more atoms selected from the group consisting of Cu, Al, and Ni, and preferably include all of Cu, Al, and Ni. It is presumed that Cu is an element that does not form a solid solution with Fe and therefore forms a cluster, Al is an element that easily forms a solid solution or a compound with Cu and forms a cluster, and Ni is an element that easily forms an intermetallic compound with Al and forms a cluster with Cu.
[0038] When a cluster contains two or more types of atoms, each cluster may be an aggregate of one type of atom or an aggregate of two or more types of atoms, but is preferably an aggregate of two or more types of atoms.
[0039] For example, when the atoms constituting a cluster include Cu, Al, and Ni, a Cu cluster, an Al cluster, and a Ni cluster may be dispersed in the amorphous phase of the Fe-based nanocrystalline soft magnetic alloy, or a cluster containing all of Cu, Al, and Ni may be dispersed, but it is preferable that a cluster containing all of Cu, Al, and Ni is dispersed.
[0040] In the microstructural observation using a three-dimensional atom probe (3DAP), the area corresponding to the cluster in the Cu distribution, the area corresponding to the cluster in the Al distribution, and the area corresponding to the cluster in the Ni distribution were If there is an overlap with the portion of the distribution that corresponds to the clusters, it is considered that clusters that contain all of Cu, Al and Ni are dispersed in the amorphous phase of the Fe-based nanocrystalline soft magnetic alloy.
[0041] As described later, the Fe-based nanocrystalline soft magnetic alloy is manufactured by heat-treating the amorphous alloy to form clusters and crystalline phases in the structure. The clusters are formed in the amorphous alloy at the initial stage of heat treatment, and in addition to growing the crystalline phase as crystal nuclei, they can also be dispersed around the crystalline phase to suppress excessive crystal growth. This is believed to result in an Fe-based nanocrystalline soft magnetic alloy containing a crystalline phase with a small average crystallite size. In addition, it is believed that the dispersion of fine clusters in the amorphous phase reduces the crystalline anisotropy and improves the magnetic permeability of the Fe-based nanocrystalline soft magnetic alloy core. A cluster containing all of Cu, Al, and Ni is preferable because it has such a high effect.
[0042] The number density of clusters in the Fe-based nanocrystalline soft magnetic alloy is not particularly limited, but is preferably 3.0×10 because a crystal phase with a small average crystallite size is likely to be formed. -4 / nm 3 More preferably, 3.5×10 -4 / nm 3 More preferably, 4.0×10 -4 / nm 3 or more, and preferably 10.0×10 -4 / nm 3 Less than or equal to 8.0×10 -4 / nm 3 Less than 6.0×10, more preferably -4 / nm 3 The following is the result.
[0043] The number density of clusters is determined by calculating the number of clusters per unit volume using three-dimensional mapping obtained by three-dimensional atom probe (3DAP) analysis of Fe-based nanocrystalline soft magnetic alloys. In this case, if one type of atom accounts for 20 atomic % or more of the atoms constituting a cluster, the cluster is counted as one cluster of that atom. Similarly, if n types of atoms account for 20 atomic % or more of the atoms constituting a cluster, the cluster is counted as one cluster containing those n types of atoms (n is an integer of 2 or more).
[0044] By setting the number density of the clusters within the above range, that is, by having many small clusters, the distance between the clusters becomes narrow. This suppresses the growth of the crystal phase that occurs with the clusters as crystal nuclei, and an Fe-based nanocrystalline soft magnetic alloy containing a crystal phase with a small average crystallite size is obtained. Therefore, the magnetic permeability of the Fe-based nanocrystalline soft magnetic alloy core tends to improve.
[0045] The number density of the clusters can be adjusted by varying the composition of the Fe-based nanocrystalline soft magnetic alloy. For example, when forming a cluster containing all of Cu, Al, and Ni, it can be adjusted by changing d, y, a, and y×(100-abcd) in the composition formula (I).
[0046] 1-1-4.Size of Fe-based nanocrystalline soft magnetic alloy ribbons The thickness and width of the Fe-based nanocrystalline soft magnetic alloy ribbon are not particularly limited as long as they can be wound to form a magnetic core of a practical shape. For example, the thickness of the ribbon may be usually 8 μm or more and 16 μm or less, and the width of the ribbon may be usually 5 mm or more and 25 mm or less.
[0047] 2. Manufacturing method for Fe-based nanocrystalline soft magnetic alloy cores The method for producing the Fe-based nanocrystalline soft magnetic alloy core according to the present embodiment is not particularly limited, and any known method may be appropriately adopted. For example, the known method may include a ribbon production step in which a molten metal having a predetermined composition is rapidly cooled and solidified by a super-quenching method to produce a ribbon of an amorphous alloy, and a heat treatment step in which the ribbon is heat-treated.
[0048] 2-1. Ribbon manufacturing process In the above method, the alloy to be subjected to the ultra-quenching method is one having the same composition as the target Fe-based nanocrystalline soft magnetic alloy, that is, an alloy having the composition represented by composition formula (I).
[0049] In the ribbon production process, the temperature of the molten metal during quenching is desirably about 50° C. to 300° C. higher than the melting point of the alloy. The ultra-quenching method is not particularly limited, and known methods such as a single roll method, a twin roll method, a rotating liquid submersion method, a gas atomization method, and a water atomization method can be used.
[0050] The preparation of the amorphous alloy ribbon by the rapid cooling method may be performed in an oxidizing atmosphere such as air, in an inert gas atmosphere such as argon, helium, nitrogen, or under vacuum conditions. The amorphous alloy ribbon obtained by the rapid cooling method preferably does not contain a crystalline phase, but may contain a crystalline phase in part.
[0051] The amorphous alloy ribbon obtained in the ribbon production process may be wound after nanocrystallization to produce a magnetic core, but it is preferable to wind the ribbon before nanocrystallization to produce a wound magnetic core and then perform a heat treatment on the wound magnetic core to nanocrystallize the alloy. This is because the alloy exhibits good workability when in the amorphous alloy stage, but when nanocrystallized by heat treatment, the workability decreases.
[0052] 2-2.Heat treatment process In the heat treatment process, the amorphous alloy constituting the ribbon is nano-crystallized. More specifically, the heat treatment process includes a process of performing heat treatment without applying a magnetic field to the amorphous alloy ribbon to nano-crystallize the amorphous alloy; a process of performing heat treatment while applying a magnetic field to the amorphous alloy ribbon to nano-crystallize the amorphous alloy; and a process of performing heat treatment without applying a magnetic field to nano-crystallize the amorphous alloy, and then performing heat treatment while applying a magnetic field to the nano-crystallized amorphous alloy ribbon; however, it is preferable to perform the heat treatment under a magnetic field application condition. By performing heat treatment while applying a magnetic field to the ribbon of the amorphous alloy having the composition represented by the general formula (I), it is possible to further increase the magnetic permeability in the high frequency range.
[0053] In addition, the formation of a fine crystalline phase progresses in the amorphous alloy by heat treatment, and in this disclosure, for convenience, an amorphous alloy including such a growing crystalline phase is also referred to as an "amorphous alloy."
[0054] The temperature during the heat treatment for promoting nanocrystallization of the amorphous alloy is not particularly limited as long as it is equal to or higher than the crystallization start temperature of the alloy, and is preferably 450°C or higher, more preferably 500°C or higher, 520°C or higher, 540°C or higher, 560°C or higher, 580°C or higher, or 600°C or higher. The upper limit of the heat treatment temperature is not particularly limited, and is preferably 700°C or lower, more preferably 680°C or lower or 660°C or lower. In the present disclosure, the heat treatment temperature means the maximum temperature reached in the heat treatment.
[0055] The holding time at the heat treatment temperature depends on the size of the amorphous alloy ribbon, etc., but from the viewpoint of uniform heating of the entire alloy and productivity, it is usually 5 minutes or more, and may be 8 minutes or more or 10 minutes or more, and is usually 5 hours or less, and may be 3 hours or less, 2 hours or less, or 1 hour or less.
[0056] When a heat treatment is performed while applying a magnetic field to a ribbon of nanocrystallized amorphous alloy, the heat treatment temperature does not need to be equal to or higher than the crystallization start temperature of the amorphous alloy, and may be a temperature lower than the crystallization start temperature. Specific heat treatment temperatures are preferably 400°C or higher, more preferably 450°C or higher, 500°C or higher, 520°C or higher, 540°C or higher, 560°C or higher, and ... ° C. or higher, 580° C. or higher, or 600° C. or higher. The upper limit of the heat treatment temperature is not particularly limited, but is preferably 700° C. or lower, and more preferably 680° C. or lower or 660° C. or lower.
[0057] The holding time at the heat treatment temperature depends on the size of the amorphous alloy ribbon, etc., but from the viewpoint of uniform heating of the entire alloy and productivity, it is usually 5 minutes or more, and may be 8 minutes or more or 10 minutes or more, and is usually 5 hours or less, and may be 3 hours or less, 2 hours or less, or 1 hour or less.
[0058] The heat treatment step may be carried out in an oxidizing atmosphere such as air, or in an inert gas atmosphere such as argon, helium, or nitrogen, or in a vacuum condition, but is preferably carried out in an inert gas atmosphere.
[0059] The strength of the magnetic field applied to the amorphous alloy ribbon is not particularly limited as long as it is sufficient to magnetically saturate the amorphous alloy, and is usually 8 kA / m or more, more preferably 16 kA / m or more, preferably 24 kA / m or more, and is usually 400 kA / m or less, preferably 320 kA / m or less, more preferably 240 kA / m or less, even more preferably 160 kA / m or less, and particularly preferably 80 kA / m or less.
[0060] The direction in which the magnetic field is applied is not particularly limited and may be any direction. For example, when a wound core is produced by winding an amorphous alloy ribbon prior to heat treatment and the wound core is then heat treated, it is preferable to apply the magnetic field in the height direction of the wound core (i.e., the width direction of the ribbon). That is, in the application of the magnetic field, the angle between the magnetic path and the direction of magnetic field application is usually 90°±15°, and from the viewpoint of improving the magnetic permeability in the high frequency range, it is preferably 90°±10°, and more preferably 90°±5°.
[0061] The present inventors speculate as follows about the reason why the magnetic permeability in the high frequency range is improved by applying a magnetic field in the heat treatment step.
[0062] First, it is believed that applying a magnetic field during heat treatment makes it easier for the magnetic domain walls to move than when no magnetic field is applied. Here, it is speculated that because the induced magnetic anisotropy imparted to the Fe-based nanocrystalline, soft magnetic alloy by the inclusion of Ni is strengthened by the application of a magnetic field, the magnetic domain walls move so that the magnetic domains expand in the direction of the applied magnetic field, reducing the coercive force, and as a result, the magnetic permeability of the Fe-based nanocrystalline, soft magnetic alloy core is improved.
[0063] Furthermore, it is presumed that when the Ni content in the Fe-based nanocrystalline soft magnetic alloy increases within the above range, the spontaneous magnetization of Ni also increases, and the magnetization direction is difficult to align even after heat treatment while applying a magnetic field, so that the effect of magnetization rotation in the magnetization process becomes large. Therefore, it is presumed that the Fe-based nanocrystalline soft magnetic alloy core according to this embodiment exhibits high magnetic permeability in the high frequency range.
[0064] 3. Applications of Fe-based nanocrystalline soft magnetic alloy cores The Fe-based nanocrystalline soft magnetic alloy core according to this embodiment can be used for various magnetic parts such as reactors, common mode choke coils, transformers, communication pulse transformers, motor cores, generator cores, yoke materials, current sensors, magnetic sensors, antenna cores, and electromagnetic wave absorbing sheets. Among these, the Fe-based nanocrystalline soft magnetic alloy core according to this embodiment is particularly suitable for use in common mode choke coils, zero-phase reactors, current transformers, and earth fault sensors, which require high magnetic permeability in the high frequency range. EXAMPLES
[0065] The present disclosure will be described in more detail below with reference to examples. However, the present disclosure is not limited to the description of the following examples as long as it does not depart from the gist of the disclosure.
[0066] The methods for measuring the relative permeability of the Fe-based nanocrystalline, soft magnetic alloy cores obtained in the following examples and comparative examples, the methods for measuring the average crystallite size of the crystalline phase in the Fe-based nanocrystalline, soft magnetic alloy, the methods for measuring the cluster number density, and the methods for observing the domain walls are as follows.
[0067] [Method of measuring relative magnetic permeability] The Fe-based nanocrystalline soft magnetic alloy core was loaded into a resin case, and then a coil was made by winding 3 turns of copper wire with a wire diameter of 0.5 mm around the resin case. Using an impedance analyzer (Keysight Technologies, Inc., E4990A), the inductance of the obtained coil was measured at frequencies of 1 kHz, 100 kHz, or 1 MHz, and Hm = 0.4 A / m, and the relative permeability of the Fe-based nanocrystalline soft magnetic alloy core was calculated based on the above formula (1). The magnetic path length l was 39 mm, and the effective cross-sectional area A was 1.8 mm. 2 , and the number of turns N is 3.
[0068] [Method for measuring average crystallite size of crystalline phase] A ribbon was unwound from an Fe-based nanocrystalline soft magnetic alloy core, and analyzed using an X-ray diffractometer (XRD) to determine the average crystallite size of the crystalline phase according to the above formula (2). In formula (2), K was 0.94 and λ was 0.178919 nm.
[0069] [Method of measuring cluster number density] A ribbon was unwound from an Fe-based nanocrystalline soft magnetic alloy core and processed to obtain a needle-shaped sample with a tip coefficient of about 10 nm. A 3D atom probe (EIKOS-UV, CAMECA) was used to observe the structure of the obtained needle-shaped sample within an area of about 60 nm x 60 nm x 16 nm, and the cluster number density was calculated from the measured volume and cluster number.
[0070] [Method of observing magnetic domain walls] Polarizing microscope using magnetic Kerr effect (Magnetic domain observation device, BH-78, manufactured by NeoArc Corporation) The magnetic domain structure of the Fe-based nanocrystalline soft magnetic alloy was observed by taking polarizing microscope photographs of the magnetic domain structure of the Fe-based nanocrystalline soft magnetic alloy using 2PI-NCC.
[0071] [Examples 1-1 to 1-5, Comparative Examples 1-1 to 1-15] An alloy ribbon was produced by the single roll method from a molten metal having the composition shown in Table 1. Specifically, a master alloy was obtained by melting and mixing the pure metals of each element weighed out to obtain the composition shown in Table 1 by the arc melting method. The molten alloy obtained by melting the master alloy was sprayed onto a roll rotating at a peripheral speed of 50 m / s under reduced pressure in an argon gas atmosphere, producing a ribbon with a width of 5 mm and a thickness of 10 μm.
[0072] The obtained ribbon was then wound to obtain a wound core with an outer diameter of 13 mm, an inner diameter of 12 mm, and a height of 5 mm. The wound core was subjected to heat treatment in a nitrogen atmosphere at the temperatures shown in Table 1 to produce an Fe-based nanocrystalline, soft magnetic alloy core. The average crystallite size of the crystalline phase in the Fe-based nanocrystalline, soft magnetic alloy and the relative permeability of the Fe-based nanocrystalline, soft magnetic alloy core are shown in Table 2.
[0073] [Table 1]
[0074] [Table 2]
[0075] From Table 2, it can be seen that the Fe-based nanocrystalline soft magnetic alloys containing Ni but not Al (Comparative Example 1-11 to Comparative Example 1-15) have a larger average crystallite size and a larger coercive force than the Fe-based nanocrystalline soft magnetic alloys containing Al and Ni but not Al (Comparative Example 1-1 to Comparative Example 1-5) and the Fe-based nanocrystalline soft magnetic alloys containing Al but not Ni (Comparative Example 1-6 to Comparative Example 1-10). As a result, it can also be seen that when the Fe-based nanocrystalline soft magnetic alloy contains Ni but not Al (Comparative Example 1-11 to Comparative Example 1-15), the Fe-based nanocrystalline soft magnetic alloy core does not exhibit sufficient relative permeability at 1 MHz.
[0076] Furthermore, from Table 2, it can be seen that the Fe-based nanocrystalline soft magnetic alloys containing Al and Ni (Examples 1-1 to 1-5) have smaller average crystallite sizes and smaller coercive forces than the Fe-based nanocrystalline soft magnetic alloys not containing Al and Ni (Comparative Examples 1-1 to 1-5) and the Fe-based nanocrystalline soft magnetic alloys that contain Ni but not Al (Comparative Examples 1-11 to 1-15). It can also be seen that the magnetic cores (Examples 1-1 to 1-5) made of ribbons of the Fe-based nanocrystalline soft magnetic alloys containing Al and Ni exhibit high relative permeability at 1 MHz.
[0077] A magnetic core made of a ribbon of an Fe-based nanocrystalline soft magnetic alloy containing Ni and not containing Al (Comparative Example 1 The reasons why the relative permeability at 1 MHz of Comparative Examples 1-11 to 1-15 is low are presumed to be the following (A) to (C).
[0078] (A) In the Fe-based nanocrystalline soft magnetic alloy containing Ni and not Al, the exchange interaction was weakened due to the large average crystallite size, and the coercivity was increased. (B) The presence of Ni enhanced the magnetocrystalline anisotropy of the crystalline phase, thereby increasing the coercive force. (C) The presence of Ni increases spontaneous magnetization in various directions within the crystalline phase, imparting induced magnetic anisotropy with different directions depending on the location, forming a complex magnetic domain structure and making it difficult for the domain walls to move, thereby increasing the coercive force.
[0079] On the other hand, the reasons why the magnetic cores (Examples 1-1 to 1-5) made of ribbons of an Fe-based nanocrystalline, soft magnetic alloy containing Al and Ni exhibit high relative permeability at 1 MHz are presumed to be the following (D) and (E).
[0080] (D) An intermetallic compound was formed from Al and Ni. This intermetallic compound formed many clusters with Cu, resulting in fine crystallites. As a result, the coercive force was reduced through exchange interactions, mitigating the effect of the increase in coercive force due to Ni. (E) The spontaneous magnetization of Ni imparts induced magnetic anisotropy, making the magnetic domain structure of the Fe-based nanocrystalline soft magnetic alloy more complex than that of a material that does not contain Ni. As a result, the magnetic domain walls become less mobile, and the effect of magnetization rotation in the magnetization process becomes greater.
[0081] [Examples 2-1 to 2-20, Comparative Examples 2-1 to 2-12] An alloy ribbon was produced by the single roll method from a molten metal having the composition shown in Table 3. Specifically, a master alloy was obtained by melting and mixing the pure metals of each element weighed out to obtain the composition shown in Table 3 by the arc melting method. The molten alloy obtained by melting the master alloy was sprayed onto a roll rotating at a peripheral speed of 50 m / s under reduced pressure in an argon gas atmosphere, producing a ribbon having a width of 5 mm and a thickness of 10 μm.
[0082] The obtained ribbon was then wound to obtain a wound core with an outer diameter of 13 mm, an inner diameter of 12 mm, and a height of 5 mm. The wound core was subjected to heat treatment in a nitrogen atmosphere at the temperatures shown in Table 3 to produce an Fe-based nanocrystalline soft magnetic alloy core. The relative permeability of the core and the average crystallite size of the crystalline phase in the Fe-based nanocrystalline soft magnetic alloy are shown in Table 4. In addition, FIG. 1 shows a graph showing the relationship between the Ni content in the Fe-based nanocrystalline soft magnetic alloy and the relative permeability of the core at 1 MHz, and FIG. 2 shows a graph showing the relationship between the Ni content in the Fe-based nanocrystalline soft magnetic alloy and the average crystallite size of the crystalline phase in the Fe-based nanocrystalline soft magnetic alloy. An approximation curve is also shown in FIG. 1.
[0083] [Table 3]
[0084] [Table 4]
[0085] Table 4 shows that the relative permeability of the magnetic core at 1 kHz and 100 kHz does not necessarily show a tendency to increase by adding Ni to the Fe-based nanocrystalline, soft magnetic alloy. On the other hand, Table 4 and Figure 1 show that the relative permeability of the magnetic core at 1 MHz increases by increasing the Ni content in the Fe-based nanocrystalline, soft magnetic alloy to more than 0.5 atomic % and 5.0 atomic %.
[0086] Also, from Table 4 and Figure 2, it can be seen that when an Fe-based nano-crystalline, soft magnetic alloy contains 1.0 atomic % or more of Ni, the average crystallite size of the crystalline phase tends to be smaller than that of an Fe-based nano-crystalline, soft magnetic alloy that does not contain Ni. Also, it can be seen that when the Ni content of an Fe-based nano-crystalline, soft magnetic alloy is less than 0.5, the average crystallite size of the crystalline phase is almost the same as that of an Fe-based nano-crystalline, soft magnetic alloy that does not contain Ni.
[0087] [Example 3-1, Comparative Examples 3-1 and 3-2] An alloy ribbon was produced by the single roll method from a molten metal having the composition shown in Table 5. Specifically, a master alloy was obtained by melting and mixing the pure metals of each element weighed out to obtain the composition shown in Table 1 by the arc melting method. The molten alloy obtained by melting the master alloy was sprayed onto a roll rotating at a peripheral speed of 50 m / s under reduced pressure in an argon gas atmosphere, producing a ribbon having a width of 5 mm and a thickness of 10 μm.
[0088] The obtained ribbon was then wound to obtain a wound core with an outer diameter of 13 mm, an inner diameter of 12 mm, and a height of 5 mm. The wound core was then heat-treated at 580°C in a nitrogen atmosphere to produce an Fe-based nanocrystalline, soft magnetic alloy core. A three-dimensional map of the Fe-based nanocrystalline, soft magnetic alloy that constitutes the core is shown in Figure 3, and the number of clusters and the cluster number density are shown in Table 5. Note that the magnification of each three-dimensional map in Figure 3 is the same.
[0089] [Table 5]
[0090] 3, it was confirmed that clusters containing Cu, Al and Ni were dispersed in the amorphous phase of the Fe-based nanocrystalline soft magnetic alloy of Example 3-1. It was also confirmed that clusters containing Cu and clusters containing Cu and Al were dispersed in the amorphous phase of the Fe-based nanocrystalline soft magnetic alloys of Comparative Examples 3-1 and 3-2, respectively.
[0091] In addition, from Table 5 and Figure 3, it can be seen that the Fe-based nanocrystalline soft magnetic alloy containing specific amounts of Al and Ni (Example 3-1) has a larger cluster number density than the Fe-based nanocrystalline soft magnetic alloy not containing Al and Ni (Comparative Example 3-1) and the Fe-based nanocrystalline soft magnetic alloy containing Al and not containing Ni (Comparative Example 3-2). From the above results, it is considered that the cluster number density can be increased by adding specific amounts of Al and Ni to the Fe-based nanocrystalline soft magnetic alloy.
[0092] [Examples 4-1 to 4-5] An alloy ribbon was produced by the single roll method from a molten metal having the composition shown in Table 3. Specifically, a master alloy was obtained by melting and mixing the pure metals of each element weighed out to obtain the composition shown in Table 6 by the arc melting method. The molten alloy obtained by melting the master alloy was sprayed onto a roll rotating at a peripheral speed of 50 m / s under reduced pressure in an argon gas atmosphere, producing a ribbon with a width of 5 mm and a thickness of 10 μm.
[0093] The obtained ribbon was then wound to obtain a wound core having an outer diameter of 13 mm, an inner diameter of 12 mm, and a height of 5 mm. The wound core was subjected to heat treatment in a nitrogen atmosphere at the temperatures shown in Table 6 to produce an Fe-based nanocrystalline, soft magnetic alloy core. The relative permeability and coercivity of the core are shown in Table 7. FIG. 4 shows a graph showing the relationship between the Ni content in the Fe-based nanocrystalline, soft magnetic alloy and the relative permeability of the core, and FIG. 5 shows a polarizing microscope photograph of the magnetic domain structure of the Fe-based nanocrystalline, soft magnetic alloy constituting the Fe-based nanocrystalline, soft magnetic alloy core obtained in Example 4-4.
[0094] [Examples 4-6 to 4-10] The Fe-based nanocrystalline soft magnetic alloy core was produced in the same manner as in Example 4-1 to Example 4-5, except that the wound core was heat-treated for 10 minutes in a nitrogen atmosphere at the temperature shown in Table 6, and then held at 480°C for another 10 minutes while a magnetic field with a magnetic field strength of 240 kA / m was applied in the height direction of the wound core (i.e., the width direction of the ribbon constituting the wound core). The relative permeability and coercive force of the magnetic core are shown in Table 7. In addition, a graph showing the relationship between the Ni content in the Fe-based nanocrystalline soft magnetic alloy and the relative permeability of the magnetic core is shown in FIG. 4, and a polarizing microscope photograph of the magnetic domain structure of the Fe-based nanocrystalline soft magnetic alloy constituting the Fe-based nanocrystalline soft magnetic alloy core obtained in Example 4-9 is shown in FIG. 5.
[0095] [Table 6]
[0096] [Table 7]
[0097] From Table 7 and Figures 4 and 5, it can be seen that by performing heat treatment while applying a magnetic field, the magnetic domain walls align in the direction of the applied magnetic field, the coercivity decreases compared to when no magnetic field is applied during heat treatment, and the relative permeability improves not only in the high frequency range but also in the low frequency range. From these, it is speculated that when a magnetic field is applied during heat treatment, the induced magnetic anisotropy imparted to the Fe-based nanocrystalline soft magnetic alloy by Ni becomes stronger due to the application of a magnetic field, causing the magnetic domain walls to move to align in one direction, decreasing the coercivity, and as a result improving the relative permeability of the magnetic core.
[0098] Furthermore, from Table 7 and Figure 4, it can be seen that as the Ni content in the Fe-based nanocrystalline, soft magnetic alloy increases within the range of 1.0 atomic % or more and less than 5.0 atomic %, the relative permeability of the magnetic core at 1 MHz increases. From this result, it is presumed that as the Ni content in the Fe-based nanocrystalline, soft magnetic alloy increases, the spontaneous magnetization of Ni also increases, making it difficult to align the magnetization even after heat treatment is performed while applying a magnetic field, increasing the ratio of rotational magnetization in the magnetization process, thereby improving the relative permeability in the high frequency range.
Claims
1. A magnetic core formed by winding a ribbon made of an Fe-based nanocrystalline soft magnetic alloy containing an amorphous phase and a crystalline phase, The Fe-based nano-crystalline, soft magnetic alloy core has a composition represented by the following composition formula (I): (F%) 1-x-y Yes x Al y ) 100-a-b-c-d Ni a M b M' c Cổ d (I) (In composition formula (I), M is one or more elements selected from the group consisting of Nb, W, Zr, Hf, Ti and Mo; M' is one or more elements selected from the group consisting of B, C and P; a, b, c and d are, in atomic %, 0.5<a<5.0, 2.0≦b≦5.0, 3.0<c<10.0 and 0<d<3.0; x and y are, respectively, 0.100≦x≦0.320 and 0.010≦y≦0.100, and satisfy 0.190≦x+y≦0.
320.
2. 2. The Fe-based nanocrystalline soft magnetic alloy core according to claim 1, wherein a in said composition formula (I) satisfies 1.0≦a≦4.
0.
3. 2. The Fe-based nanocrystalline soft magnetic alloy core according to claim 1, wherein a in said composition formula (I) satisfies 1.5≦a≦4.
0.
4. 2. The Fe-based nanocrystalline soft magnetic alloy core according to claim 1, wherein a in said composition formula (I) satisfies 2.0≦a≦3.
0.
5. 2. The Fe-based nanocrystalline soft magnetic alloy core according to claim 1, wherein the average crystallite size of the crystalline phase is 12.0 nm or less.
6. Clusters are dispersed in the amorphous phase, and the number density of the clusters is 3.0×10 -4 / nm 3 The Fe-based nanocrystalline soft magnetic alloy core according to claim 1 .
7. A magnetic part comprising the Fe-based nanocrystalline soft magnetic alloy core according to any one of claims 1 to 6.
8. A method for producing an Fe-based nanocrystalline soft magnetic alloy core according to any one of claims 1 to 6, comprising the steps of: a ribbon-producing step of producing a ribbon of an amorphous alloy by rapidly solidifying the molten metal having the composition represented by the general formula (I) by a super-quenching method; a heat treatment step of heat treating the ribbon; A method for producing an Fe-based nanocrystalline soft magnetic alloy core, comprising:
9. The method for producing an Fe-based nanocrystalline, soft magnetic alloy core according to claim 8 , wherein the heat treatment step is carried out under a magnetic field application condition.
Citation Information
Patent Citations
Soft magnetic alloy
JP2004002949A